1989
DOI: 10.1176/appi.psychotherapy.1989.43.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder Apparently Related to Abortion

Abstract: This case study presents a young woman who developed a severe obsessive-compulsive disorder after a routine medical procedure. It is suggested that this procedure brought back repressed guilt from three abortions and thus led to the onset of symptoms. The case is discussed in relationship to available research and theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The possibility of a delayed emotional response occurring years later is also suggested (Speckhard & Rue, 1992;McGraw, 1989;Stone-Joy, 1985). Kenyon (1986) noted that a reactive depression may manifest itself during the "birthday" of the child, or the "anniversary" date of the abor-tion.…”
Section: Mourning a F E R An Elective Abortionmentioning
confidence: 99%
See 3 more Smart Citations
“…The possibility of a delayed emotional response occurring years later is also suggested (Speckhard & Rue, 1992;McGraw, 1989;Stone-Joy, 1985). Kenyon (1986) noted that a reactive depression may manifest itself during the "birthday" of the child, or the "anniversary" date of the abor-tion.…”
Section: Mourning a F E R An Elective Abortionmentioning
confidence: 99%
“…Peppers (1987) found that the ambiv-alence in the decision making also can affect the grief and mourning experienced after the abortion. McGraw (1989) found that women who based their decision on what parents or the parmer wanted were at greater risk for a postabortion reaction. Stone-Joy (1985) reported that women who decided to abort in haste, secrecy, and isolation had the greatest desire to stop thinking about the event as quickly as possible and were more likely to experience a greater degree of loss after the abortion.…”
Section: The Guiltmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with both conditions are preoccupied with the integrity of living beings (humans or animals), often believing that something terrible can happen to them by their omission, such as major accidents or disasters in OCD, hunger or poisoning in animal hoarding, and serious diseases in both. They also have strong-held moral values, including repugnance of abortion- and euthanasia-related themes in OCD (12,13) and animal hoarding (14), respectively.…”
Section: Introductionmentioning
confidence: 99%